E-commerce Platform of Ikat Woven for East Nusa Tenggara Underdeveloped Rural Society - FX Gugus Febri Putranto; Christiayu Natalia (Sekolah Pascasarjana Universitas Brawijaya, 2018)
Rural economic plays an important role in the development of a region. As stated in the third Nawacita, Indonesian government wants to build Indonesia from the periphery. East Nusa Tenggara Province, which most of its region are underdeveloped rural, requires innovation to strengthen its economic potential. Based on the data from Statistics Indonesia, in 2014-2016, economic growth in East Nusa Tenggara Province continues to increase, while the proportion of the poor has increased greatly during that period. Thus, solutions to reduce poverty should be taken. Agriculture as a on economic sector in rural region, could not give the optimum value added, since the most of rural society in East Nusa Tenggara are subsistent farmer. It is necessary to improve other sectors that have the potential to generate optimal value added for rural society. Ikat woven industry is a part of custom which could not be separated from the daily life of the society. However, ikat woven’s marketing is very limited. Therefore, innovation is needed to open the access into the market through an e-commerce platform that directly connected with the ikat woven producers. The synergy of various parties needs to be done, the government needs to facilitate the ikat woven e-commerce platform and coordinate its use. Cooperation with Statistics Indonesia can be done to collect data of the weaving producers and their commodities. The private sector is also expected to participate through investment to increase productivity and diversification of ikat woven products.